1994
DOI: 10.1111/j.1365-2621.1994.tb05543.x
|View full text |Cite
|
Sign up to set email alerts
|

Konjac Flour Gel as Fat Substitute in Low‐fat Prerigor Fresh Pork Sausage

Abstract: Prerigor trimmings from four lean cuts of pork carcasses (n = 3) were used to manufacture three replications of low-fat (10%) fresh pork sausage containing konjac flour gel, at 0, 10 or 20% levels and compared to a 40% fat control. Treatment sausages showed equal or improved cooked yields, slightly higher shear force (kg/g) and sensory textural attributes, but rated slightly lower in juiciness. As konjac flour gel levels increased, shear force and sensory textural attributes became mom like the control. Storag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(35 citation statements)
references
References 17 publications
4
31
0
Order By: Relevance
“…Allo-Kramer shear values increased as the level of chickpea flour in the formulation increased suggesting a strong gel structure formation within the bologna matrix. In contrast to effects seen with chickpea flour, a previous study showed that increased level of konjac flour gel in low-fat pork sausage had an inverse relationship with A-K shear force (Osburn & Keeton, 1994). The control bologna sample showed the least springy and chewy mean values for instrumental texture profile analyses (TPA; Table 5).…”
Section: Instrumental Texture Propertiesmentioning
confidence: 89%
“…Allo-Kramer shear values increased as the level of chickpea flour in the formulation increased suggesting a strong gel structure formation within the bologna matrix. In contrast to effects seen with chickpea flour, a previous study showed that increased level of konjac flour gel in low-fat pork sausage had an inverse relationship with A-K shear force (Osburn & Keeton, 1994). The control bologna sample showed the least springy and chewy mean values for instrumental texture profile analyses (TPA; Table 5).…”
Section: Instrumental Texture Propertiesmentioning
confidence: 89%
“…The color of meat products is a very important for choice by consumers and is affected by pH, additives, and pigments through cooking (Osburn and Keeton, 1994). The instrumental color of the batter and sausages samples is presented in Cooking yield and emulsion stability Significant differences were found in cooking yield among the samples ( Table 3).…”
Section: Instrumental Color Evaluationmentioning
confidence: 96%
“…It is a perennial plant native to south-east Asia, which has been cultivated in Asia for c. 2000 years for use of the corm as food and medicine (Ohwi 1965;Kurihara 1979;Liu et al 1995;Long 1995;Brown 2000). Glucomannan, a polysaccharide with a high molecular weight, provides the unique rheological and gelling properties of konjac flour, making it an important ingredient in many food products as a thickening and heat-stable gelling agent (Tye 1991;Thomas 1997) and as a fat substitute in processed meat products (Osburn & Keeton 1994;Lin & Huang 2003). Konjac flour and glucomannan are used as a dietary fibre and clinical trials have shown that glucomannan lowers cholesterol and blood sugar levels (Arvill & Bodin 1995;Doi 1995).…”
Section: Introductionmentioning
confidence: 99%